Boundary value problems for semilinear differential inclusions of fractional order in a Banach space. Issue 4 (12th March 2018) - Kamenskii, Mikhail; Obukhovskii, Valeri; Petrosyan, Garik; Yao, Jen-Chih
Abstract : In the present paper, we show that the solution set of a fractional order semilinear differential inclusion in a Banach space has the topological structure of an -set. This result allows to apply a fixed point result for condensing multimaps to the translation multioperator along the trajectories of such inclusion and to prove the existence of solutions satisfying periodic and anti-periodic boundary value conditions. An example concerning with a fractional order feedback control system is presented.